Bentuk Perlindungan Hukum bagi Nasabah terhadap Pembobolan Rekening Nasabah oleh Pegawai Bank - Riadhi Tedi Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2020)
Legal protection for customers as consumers in the banking sector is an urgent matter, considering that there have been many incidents of theft of money through customer account hacking, even by bank employees themselves. The type of banking crime observed in this study is a banking crime involving bank employees. The choice of this type of crime is based on the fact that the majority of banking crimes that have recently occurred are committed by people involved as bank management team, so the causative factors need to be found immediately in order to determine the appropriate preventive measures. Based on this, the study uncovers two issues: (1) the form of legal protection for the bank customer regarding the theft of their money through the hacking of their account by a bank employee and (2) the bank’s liability for the theft of money that is committed through hacking of the customer account by bank the employee itself. This study uses a normative research method with a statute approach, a case approach, and a conceptual approach. The results showed that legal protection for bank customer with regard to the theft of money through hacking of customer account by bank employee was realised in the form of a warning against the offender of the hacking. The liability of the bank for the hacking of the customer account by its employee is through the collection and management of customer funds who was the victim of such hacking was carried out based on the principle of trust to ensure the safety of public deposits in the bank.